Chronic opioid induced constipation in patients with nonmalignant pain: challenges and opportunities. (July 2015) - Nelson, Alfred D.; Camilleri, Michael
With the recent introduction and approval of medications directed at the treatment of opioid induced constipation (OIC) in patients with nonmalignant pain, there is increased interest and understanding of the unmet need and opportunities to enhance patient management. The high incidence of OIC is associated with rapid increase of narcotic analgesic prescriptions for nonmalignant chronic pain. This review addresses briefly the mechanisms of action of opioids that lead to OIC, the differential tolerance of gastrointestinal organs to the effects of opioids, the size and scope of the problem, the definition and outcome measures for OIC, current differential diagnosis and management algorithms, and the pharmacology and efficacy of treatments for OIC in patients with nonmalignant pain.